Intracellular Signalling Pathways Associated with the Glucose-Lowering Effect of St36 Electroacupuncture in Streptozotocin-Induced Diabetic Rats. Issue 5 (October 2015) - Tzeng, Chung-Yuh; Lee, Yu-Chen; Ho, Tin-Yun; Chen, Ying-I; Hsu, Tai-Hao; Lin, Jaung-Geng; Lee, Kuan-Rong; Chang, Shih-Liang
Background and Aim: Previous animal studies have reported a glucose-lowering effect of electroacupuncture (EA) and suggested that the mechanisms are closely related to intracellular signalling pathways. The aim of this study was to screen for potential intracellular signalling pathways that are upregulated by EA at ST36 bilaterally in rats with diabetes mellitus (DM) using microarray analysis. Methods: Streptozotocin (STZ)-induced diabetic rats were randomly assigned to experimental (EA, n=8) or control (non-EA, n=8) groups. Plasma glucose levels were measured at baseline and after 30 and 60 min, and microarray analysis was performed on samples of gastrocnemius muscle. Results: Relative to baseline values, EA significantly reduced plasma levels of glucose at 30 and 60 min. The microarray pathway analysis showed that cell adhesion molecules and type 1 DM gene sets were both upregulated in EA versus non-EA groups (p<0.05). Conclusions: Cell adhesion molecules might be related to the glucose-lowering effect induced by EA in rats with STZ-induced type 1 diabetes. Further research will be required to examine the involvement of related intracellular signalling pathways.